Diabetes and SARS-CoV-2–Is There a Mutual Connection? - Jedrzejak, Anna P.; Urbaniak, Edyta K.; Wasko, Jadwiga A.; Ziojla, Natalia; Borowiak, Malgorzata (Frontiers in Cell and Developmental Biology, 2022)
Graphical Abstract